2019
DOI: 10.3389/fcell.2019.00355
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Involvement in Migration, Invasion and Metastasis

Abstract: Mitochondria in addition to be a main cellular power station, are involved in the regulation of many physiological processes, such as generation of reactive oxygen species, metabolite production and the maintenance of the intracellular Ca 2+ homeostasis. Almost 100 years ago Otto Warburg presented evidence for the role of mitochondria in the development of cancer. During the past 20 years mitochondrial involvement in programmed cell death regulation has been clarified. Moreover, it has been shown that mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 186 publications
(256 reference statements)
0
86
0
Order By: Relevance
“…Therefore, FICZ might participate to repair the B[a]P‐induced DNA damage. Bcl2 participates in apoptosis induced by mitochondrial leakage of cytochrome c and plays an important role in the regulation of ROS production and cell migration (Denisenko, Gorbunova, & Zhivotovsky, 2019; Perianayagam, Madias, Pereira, & Jaber, 2010). The regulations of P53 to cell cycle, DNA repair, and apoptosis dependent on ROS generation and caspase activation in mitochondria (Schuler & Green, 2001; Sionov, Hayon, & Haupt, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FICZ might participate to repair the B[a]P‐induced DNA damage. Bcl2 participates in apoptosis induced by mitochondrial leakage of cytochrome c and plays an important role in the regulation of ROS production and cell migration (Denisenko, Gorbunova, & Zhivotovsky, 2019; Perianayagam, Madias, Pereira, & Jaber, 2010). The regulations of P53 to cell cycle, DNA repair, and apoptosis dependent on ROS generation and caspase activation in mitochondria (Schuler & Green, 2001; Sionov, Hayon, & Haupt, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial impairments have been associated to several pathologies not only limited to metabolic diseases or myopathies, but including cancer (Vyas et al, 2016;Denisenko et al, 2019), pulmonary hypertension (Chen et al, 2019) and neurodegenerative disorders such as Alzheimer's and Parkinson's disease (Kim and Mook-Jung, 2019;Tapias, 2019). Thus, further understanding of mitochondrial surveillance mechanisms might help to establish therapeutic interventions for treatment of mitochondrial pathologies.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It has been shown that cellular metabolism is involved in cell migration and eventually in metastasis, and that addiction of cancer cells on mitochondria depends on the cancer type (summarized by [43,58,59]). Being at the crossroad of glycolysis, lipid and oxidative metabolism [19,60], mGPDH controls important metabolic functions and may be involved in metabolic adaptations during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%